Atypical glandular cells: Help or hindrance - Narang, Sanjeev; Dargar, Parul; Singh, Anjali; Malhotra, Apurva (Journal of Pathology of Nepal, 2018)
Background: Atypical glandular cell is still a rare diagnosis despite refinement of the cytomorphologic criteria. This study aims to evaluate the follow up biopsies of cases diagnosed as atypical glandular cells on pap smears and to correlate with histological findings. Materials and Methods: This is a retrospective study over a period of 7 years based on cyto-histopathological correlation of AGC diagnosed cases. Results: Cytodiagnosis of atypical glandular cells was given in 212(0.05%), and 140 (0.66%) patients underwent biopsy. Among these 74(52%) were benign and 66(47%) neoplastic. Of the 39 cases reported as AGC favor neoplastic, 24(61%) showed malignancy with a positive predictive value of 61.5% and of the101 cases classified as AGC-NOS on cytology, 59 (58%) cases showed benign features with a negative predictive value of 58.4 percent. Conclusion: Our study highlights the immediate need of histological follow up of patients diagnosed with AGC. It is important because the range of diseases associated is very variable and includes benign as well as malignant conditions.